2014
DOI: 10.1128/jcm.03521-13
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Molecular Diagnosis of Hepatitis Delta Virus Infection: Results of a French National Quality Control Study

Abstract: A French national quality control study for the serological and molecular diagnosis of hepatitis delta virus (HDV) was organized. Total HDV antibodies were properly detected by all laboratories; 8/14 laboratories failed to detect low titers of IgM, and 6/11 failed to quantify and/or underestimated the RNA viral load in several samples. These discrepancies are likely related to the molecular diversity of HDV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Indeed, one most important practical consequence of the molecular diversity of HDV in clinical routine is the failure of commercial and “in‐house” assays to properly detect or quantify plasmatic HDV RNA in patients. Particularly, HDV RNA viral loads have been dramatically underestimated by most assays in patients infected with strains of African genotypes (HDV‐1a, HDV‐1b, and HDV‐5 to HDV‐8) . This is also a critical challenge in the management of patients in the era of the development of new specific anti‐HDV drugs such as entry and farnesyl transferase inhibitors and nucleic acid polymers …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one most important practical consequence of the molecular diversity of HDV in clinical routine is the failure of commercial and “in‐house” assays to properly detect or quantify plasmatic HDV RNA in patients. Particularly, HDV RNA viral loads have been dramatically underestimated by most assays in patients infected with strains of African genotypes (HDV‐1a, HDV‐1b, and HDV‐5 to HDV‐8) . This is also a critical challenge in the management of patients in the era of the development of new specific anti‐HDV drugs such as entry and farnesyl transferase inhibitors and nucleic acid polymers …”
Section: Discussionmentioning
confidence: 99%
“…The quantification of HDV RNA has become a major diagnostic issue, for both the management of patients and the evaluation of new specific anti‐HDV therapies, which are currently in progress. Recent studies have shown that in comparison to the FNRL‐HDV consensus assay, many in‐house and commercial assays dramatically underestimate HDVL and even fail to detect HDV‐RNA . These discrepancies among assays were shown to be mainly related to the high genetic diversity of HDV and to primers and probes poorly adapted.…”
Section: Discussionmentioning
confidence: 99%
“…It is based on TaqMan real‐time reverse‐transcriptase polymerase chain reaction (RT‐PCR) technology and capable of quantifying RNA load for most, if not all, known strains of HDV . Several other in‐house and commercial assays have been developed in specialized laboratories using real‐time RT‐PCR technologies, but they performed poorly compared to the FNRL‐HDV assay in recent studies . The high genetic variability of HDV is a key factor in the discrepancies observed for these tests, which, furthermore, suffer from a lack of standardization.…”
mentioning
confidence: 99%
“…Particularly, African HDV genotypes (i.e., HDV-1 and HDV-5 to -8) are poorly quantified by almost all available assays and are either undetected or dramatically underestimated (11). These different genotypes originally had a specific geographic distribution; however, due to ancient or recent migrations of populations, this genetic variability is now encountered in different countries worldwide (9)(10)(11)(17)(18)(19)(20)(21)(22)(23)(24)(25). In this respect, France, where genotypes HDV-5 to -8 representing 20% of spreading strains were characterized, is an outstanding example (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…However, very recently we showed that most of them dramatically underesti-mated or failed to detect/quantify positive HDV RNA samples, especially from patients infected with strains of African origin (HDV-1 and HDV-5 to -8) (9)(10)(11), highlighting the lack of efficient tools to routinely monitor HDVL for therapeutic management of infected patients.…”
mentioning
confidence: 99%